When evidence alone is not enough: the problem, policy and politics of water fluoridation in England. (1st August 2021) - Lowery, Gary; Flinders, Matthew; Gibson, Barry J.
Abstract : Background: Tooth extractions are the most common cause of hospital admissions for children in England. Water fluoridation has the potential to reduce this number by 60%, is backed by the scientific and public health communities, and yet is currently consumed by only 10% of the population.Aims and objectives: This 'evidence-policy gap' is explored through Kingdon's 'multi-streams approach' which provides insights into the circumstances under which water fluoridation has made it onto the political agenda, the rationale underpinning opponent and advocate policy positions, and the role of the political arena in fostering or hindering policy action.Methods: Over 100 primary documents were reviewed to develop an understanding of the scientific and ethical arguments for and against water fluoridation, as well as to identify how they have all historically sought to mobilise their policy preferences. Eleven consultations were also conducted with stakeholders as part of the knowledge exchange process.Findings: The key finding of this research is that evidence is only likely to trigger policy change if it emerges into a receptive sociopolitical context. In substantiating this claim we identify evidence not of an 'evidence-policy gap' but of a more complex and multidimensional 'evidence-policy-politics gap'.Discussion and conclusions: The findings contribute to a range of debates in relation to: (1) the apparent irreconcilability of background ideas about what ought to form the basis of public health policymaking; (2) the presence of differing evidential standards that create an uneven playing field; and (3) the central underpinning role of politics in public health policymaking.